Omnidirectional autonomous entry guidance based on 3-D analytical glide formulas. (November 2016) - Yu, Wenbin; Chen, Wanchun; Jiang, Zhiguo; Liu, Xiaoming; Zhou, Hao
Abstract: An autonomous entry guidance law is developed based on 3-D analytical glide formulas, where the downrange formula is used to plan the longitudinal reference profile in order to meet the downrange and final energy requirements, and the crossrange formula is used to regulate the bank reversals in order to eliminate the crossrange error. As the analytical glide formulas ignore the effects of the Earth׳s rotation, a series of strategies is proposed for compensating these effects, which provides the guidance with the capability of steering the hypersonic glide vehicle with high Lift to Drag ratio ( L / D ) to any place of the world accurately. The compensation strategies can be summarized into two parts: (1) the reference profiles are properly adjusted by roughly evaluating the effects of the Earth׳s rotation on the aerodynamic profiles over the whole flight, which can compensate most of the effects; (2) the current effects are accurately evaluated and then the guidance commands are slightly modulated for compensating the remaining effects. Due to careful design, the strategies will not result in drastic changes in the Angle of Attack (AOA) and can keep the bank angle almost constant during most of flight. Highlights: An autonomous entry guidance law based on 3-D Analytical Glide Formulas is developed for high-L/D hypersonic glide vehicle. The generalized aerodynamic forces are introduced to compensate the effects of the Earth's rotation. A careful method of planning the generalized aerodynamic profiles is designed such that the AOA and bank angle remain almost constant in steady glide phase. α 2 - correction algorithm is proposed for improving the accuracy of final altitude.